2014
DOI: 10.1161/circulationaha.114.012717
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Clinical Outcome of Major Adverse Cardiac Events in Survivors of Infective Endocarditis

Abstract: Background-Substantial infective endocarditis (IE)-related morbidity and mortality may occur even after successful treatment. However, no previous study has explored long-term hard end points (ie, stroke, myocardial infarction, heart failure, cardiovascular death) in addition to all-cause mortality in IE survivors. Methods and Results-A nationwide population-based cohort study was conducted among IE survivors identified with the use of the Taiwan National Health Insurance Research Database during 2000 to 2009.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 41 publications
4
83
1
2
Order By: Relevance
“…In the ICE‐PCS cohort, in‐hospital mortality was associated with IE complications of prosthetic or mitral valve IE, pulmonary edema, paravalvular complication, and S aureus infection 1. Longer term studies have demonstrated higher mortality rates in IE patients beyond the index hospitalization, predominantly due to noncardiovascular conditions 4, 5. A recent study from Taiwan using administrative claims also found higher risk of cardiovascular events in long‐term follow‐up 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the ICE‐PCS cohort, in‐hospital mortality was associated with IE complications of prosthetic or mitral valve IE, pulmonary edema, paravalvular complication, and S aureus infection 1. Longer term studies have demonstrated higher mortality rates in IE patients beyond the index hospitalization, predominantly due to noncardiovascular conditions 4, 5. A recent study from Taiwan using administrative claims also found higher risk of cardiovascular events in long‐term follow‐up 5.…”
Section: Discussionmentioning
confidence: 99%
“…Longer term studies have demonstrated higher mortality rates in IE patients beyond the index hospitalization, predominantly due to noncardiovascular conditions 4, 5. A recent study from Taiwan using administrative claims also found higher risk of cardiovascular events in long‐term follow‐up 5. In our previous study of 1‐year survival after prosthetic valve endocarditis, the rate of mortality remained high for the first 4 months after admission for IE in patients treated with medical therapy alone or in combination with surgery 16…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This database contains detailed medical claims data from almost all of Taiwan's inhabitants (average 23 million) since 1995 and has been described in detail previously. 17,18 We used International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) codes to identify important comorbid conditions. We first selected patients with 1 primary discharge diagnosis or 2 outpatient diagnoses of diabetes (ICD-9-CM code 250.x).…”
Section: Study Population and Designmentioning
confidence: 99%
“…The relationship between IE and cancer had been reported, however, IE survivors with concomitant use of cardiovascular medication may impact on the results (11). In addition, IE is a complicated and serious infection disease and has a high mortality rate in both in-hospital and long-term follow-up (12,13). This makes the categorical relationship between IE and cancer more difficult to clarify.…”
mentioning
confidence: 99%